The effects of different water table conditions in peat soils on selected soil chemical properties and growth response of Brassica rapa l. var. chinensis - Azhar, Nadia Maisarah; Adam, Salwa; Boll Kassim, Nur Qursyna (GADING Journal of Science and Technology, 2024)
The fluctuating water table in peat systems induces alternating aerobic and anaerobic conditions, thereby influencing specific soil chemical properties and subsequently impacting nutrient uptake efficiency by plants cultivated in such environments. This study aims to analyse selected soil chemical properties and evaluate the growth performance of Brassica rapa L. var. Chinensis cultivated in peat soils subjected to varying water table levels. Peat soil samples were collected from Tangkak, Johor, Malaysia. Experimental treatments comprised four distinct water table levels: T0 (control) at 0 cm; T1 at 5 cm; T2 at 10 cm; and T3 at 15 cm below the soil surface, respectively. The samples were arranged in a Completely Randomised Design (CRD) within a greenhouse environment. Results revealed significant differences in soil pH, soil available phosphorus (P), and soil exchangeable potassium (K) and magnesium (Mg) among treatments. Multiple comparisons analysis indicated that T3 (peat soil with a 15 cm water table level) exhibited the highest concentrations of soil available P, soil exchangeable K and Mg, as well as a higher soil pH compared to other treatments. Correlation tests between treatments unveiled significant interactions among soil exchangeable K, calcium (Ca), and Mg, as well as soil pH. However, no substantial differences were observed in the growth performance of Brassica rapa L. var. Chinensis across treatments. Consequently, this study suggests dynamic fluctuations in soil chemical properties, particularly soil pH, exchangeable K, Ca, and Mg, in peat soils at various water table levels, without significant effects on the growth of Brassica rapa L. var. Chinensis.